THE DYNAMICS OF PARENT-CHILD RELATIONSHIP WITH ONLINE GAME ADDICTS - Aufizzahra As Syafiyah, Aufizzahra; Primanita, Rida Yanna (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Online gaming addiction refers to behaviors that involve excessive use of online games that cause emotional or social problems. This research aims to find out how the description of addiction, the dynamics of parent-child relationship with online game addicts contained in the subchapters of the respondent's background, description of addiction and supporting addiction theories, description of parent and child relationships that are specialized in discussions related to: parenting, attachment style. This research uses a qualitative approach. The participants of this research include online game addicts domiciled in Bukittinggi City, West Sumatra, totaling 2 people and collection through semi-structured interviews with research subjects and the closest people related to the research subject. The data obtained shows the results that Subjects 1 and 2 can be classified into the category of online game addiction. Subject 1's parents applied a parenting style that fell into the permissive category with a preoccupied attachment style. The theory underlying Subject 1's addictive behavior is Freud's psychoanalytic theory, in which id is more dominant. Subject 2's parents apply parenting that falls into the neglectful category with a dismissing attachment style. The underlying theory of Subject 2's addictive behavior is classical theory in which addiction arises due to repeated use. Suggestions can be made for future research to expand the scope of similar discussions by examining various other factors that can influence online game addiction. Some factors that could be explored involve life satisfaction, loneliness, self-esteem, social skills, self-control, and interpersonal relationships.